Stability analysis and full-scale test of a new recyclable supporting structure for underground ecological granaries. (1st August 2019) - Pan, Yanhui; Fang, Hongyuan; Li, Bin; Wang, Fuming
Highlights: A new rigid-flexible composite recyclable supporting structure is proposed. Numerical calculation and full-scale test are developed for the new supporting system. Mutual validation of full-scale test and finite element result is carried out. The full-scale test shows that the new supporting system is stable. Abstract: The underground ecological granary has the advantages of low temperature, heat insulation, safety, and mechanization operation of moving grain in and out of the granary. It is the most suitable environmentally friendly warehouse for long-term grain storage at present. Traditional underground granary supporting structures mostly use cement materials and present disadvantages including long periods of construction, difficulties in repairing cracks and leakages, and difficulties in demolition. Based on a steel skeleton supporting structure and flexible waterproof polymers, this paper proposed a new rigid-flexible composite recyclable supporting structure for underground storage granaries. Through the use of ABAQUS software, this paper established a three-dimensional finite element numerical model for excavation of the new supporting structure; analyzed stresses and deformations of the steel pile, middle beam, and steel plate and ground settlement at different excavation steps; and checked the stability of the new supporting structure. Additionally, considering a certain ecological storage granary in Zhongmou County of Henan Province, this paper developed a full-scale test for the new supporting structure. By monitoring the stresses of the supporting structure and ground settlement during excavation, it was concluded that the field monitoring results basically matched the results from numerical simulation. The new supporting structure has the advantages of good stability, quick construction, recyclable usage, low cost, and broad application prospects.